Comparación de densidades poblacionales en la productividad del cultivo de sorgo (Sorghum bicolor L. Moench.) en el Ecuador - CAÑIZARES RAMIREZ, ALEMBER JOSE (2023)
This document reports relevant information on the population density and yield of sorghum (Sorghum bicolor L. Moench). The yield of sorghum depends on the planting season and the planting density, since it is a highly sensitive crop to different types of soil and climatic conditions, and its yield depends on the crop conditions. In the preparation of this document, the information obtained from updated texts, journals, virtual libraries and scientific articles contributed to the production of this information and served as practical elements to interpret, summarize and analyze the collection of information to obtain relevant research. The conclusion is that sorghum cultivation is an important source of raw material for the world, and Mexico and the United States are the main exporters of this crop, innovation on technology to grow sorghum is limited, population density is the main factor affecting performance. This is because, depending on the type of sorghum, the number of plants per hectare is required. Its benefits are due to the fact that it normalizes and improves the physiological conditions of the plant to obtain optimal yields. The population density of sorghum depends on the planting distance, being recommended a spacing between rows of 0.5 m, with 20-25 plants per linear meter, a population density of 200,000 plants/ha and an average grain yield of about 6.0 tons. /Ha